Opinions and experiences on the provision of care to people with mental illnesses: a qualitative study with Doctor of Pharmacy graduates after a rotation in psychiatry - Monica Zolezzi (10115698) (2023)
Background Pharmacists are vital to optimizing therapy of people with mental illnesses. Limited knowledge, lack of confidence, and mental health-related stigma can lead to pharmacists’ reluctance in the provision of pharmaceutical care to this population. Advanced pharmacy practice experiences (APPE) in mental health have been reported as valuable learning opportunities to overcome these challenges. Aim This study aimed to explore PharmD graduates’ perceived preparedness, attitudes, beliefs, and opinions on influencing factors for the provision of pharmaceutical care to people with mental illnesses after completing an APPE rotation in psychiatry. Method All PharmD graduates who had completed a rotation in psychiatry were invited to participate in semi-structured interviews. An interview guide was developed based on a literature review. A total of 11 PharmD graduates agreed to participate in the interviews, which were recorded, transcribed, and analysed inductively using thematic analysis and following a phenomenological approach. Results Five themes were identified: Prior familiarity to mental health, opinions on the rotation, views on stigma, rotation’s areas of improvement, and the positive impact of the rotation on practice. Although participants started the psychiatric rotation with low confidence and a sense of apprehension, they described their experience as unique, eye-opening, and insightful. Familiarity with mental health conditions before the rotation were perceived as a challenge to achieving full confidence in mental health care provision. Conclusion For the most part, the APPE in psychiatry was viewed as a positive opportunity for enhancing the PharmD graduates’ insight, knowledge, and skills for pharmaceutical care provision to people with mental illnesses. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-023-01646-1